An Apprach to Determining the Foreign Language Readiness of Graduates of Kazakhstani Universities in a Professional Environment (Journal of Educational Sciences, 2021)
An issue of foreign language training of professionals for various fields of activity is sharply raised today in Kazakhstan. Modern society and the state put forward basic requirements for the training of personnel by the country’s universities. They note the need to give impetus to the development of the vocational education system for the training of modern Kazakhstani specialists. This article is devoted to the consideration of the role of the English language in the modern world. The article discusses the names of scientists, who were the developers of professional oriented teaching, their contributions, thoughts and ideas. There were the works of the methodologists that made it possible to acquaint the world with the peculiarities and methods of teaching foreign languages for specially oriented purposes. Similar trends can be traced even today, without losing their relevance. The article describes the authors’ attempt to determine the quality of training of modern specialists in the republic, the problems that spe- cialists face in training, the disadvantages and advantages of foreign language training. Many graduates form different universities took part in survey. 100 young professionals took part in the survey. The sur- vey results and recommendations are presented in the article. 95% of graduates note the important role and relevance of language competencies: the presence of language practice in the specialty; the ability to make presentations and speak at symposia, conferences in the specialty; the ability to establish in the language high-quality interpersonal communication with foreign colleagues; knowledge of professional terminology in the language, etc.Key words: English, professionally oriented education, competent specialist, communicative com- petence, multilingual specialists.